2020
DOI: 10.1002/mdc3.12936
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference in Autonomic Dysfunction Between Multiple System Atrophy Subtypes?

Abstract: Background Autonomic dysfunction forms the diagnostic cornerstone in MSA. Data are limited on autonomic dysfunction differences between the two subtypes, MSA‐C and MSA‐P. Objectives To assess autonomic dysfunction in MSA subtypes and Parkinson's disease (PD) and compare it to healthy controls. Methods We conducted a cross‐sectional study. A validated questionnaire (Scales for Outcomes in Parkinson's Disease–Autonomic Dysfunction; SCOPA‐AUT) was used for symptom screening. Cardiovascular autonomic testing inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Endoscopic evaluation of swallowing in patients with MSA and PD by Vogel et al ( 64 ) found that patients with MSA exhibited more symptoms suggestive of oral-phase disturbances (premature spillage, swallowing debris) than patients with PD, which could be the main phenotype of dysphagia in MSA. We found that the incidence of sexual dysfunction was higher in MSA than in PD, which was partially in agreement with Garg et al ( 65 ), who used SCOPA-AUT to assess autonomic dysfunction in MSA and PD and found the incidence of sexual dysfunction in MSA was higher than in PD in males, although this difference did not reach statistical significance. Patients with MSA were more likely to suffer from a lack of motivation, while patients with PSP were more likely to suffer from forgetting things or events.…”
Section: Discussionsupporting
confidence: 91%
“…Endoscopic evaluation of swallowing in patients with MSA and PD by Vogel et al ( 64 ) found that patients with MSA exhibited more symptoms suggestive of oral-phase disturbances (premature spillage, swallowing debris) than patients with PD, which could be the main phenotype of dysphagia in MSA. We found that the incidence of sexual dysfunction was higher in MSA than in PD, which was partially in agreement with Garg et al ( 65 ), who used SCOPA-AUT to assess autonomic dysfunction in MSA and PD and found the incidence of sexual dysfunction in MSA was higher than in PD in males, although this difference did not reach statistical significance. Patients with MSA were more likely to suffer from a lack of motivation, while patients with PSP were more likely to suffer from forgetting things or events.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of drooling ranged from 5% to 80% (Figure 4). In 18 articles, a control group was included, although three of these did not investigate whether there was a difference between the groups 40‐42 . However, 15 articles did analyse the difference between the control and patient groups, and 14 of these showed a significant difference 1,35,36,43‐53 .…”
Section: Resultsmentioning
confidence: 99%
“…In 18 articles, a control group was included, although three of these did not investigate whether there was a difference between the groups. [40][41][42] However, 15 articles did analyse the difference between the control and patient groups, and 14 of these showed a significant difference. 1,35,36,[43][44][45][46][47][48][49][50][51][52][53] The presence of drooling in the control group ranged from 0% to 17%.…”
Section: Ta B L E 2 Continuedmentioning
confidence: 99%
“…In addition, the count of lymphocytes reflected the nutritional status predicting the prognosis of many diseases ( 24 , 25 ), while the nutritional indicators did not have a significant difference between the two groups. Moreover, the autonomic nervous system was reported to influence the distribution of lymphocytes previously, while most patients with MSA exhibited autonomic dysfunction ( 26 ). The alterations in neuroregulatory factors in MSA patients probably affect the distribution of immune cells ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%